Taking Baby Steps : How Patients and Fertility Clinics Collaborate in Conception - Madeira, Jody Lynee (Book collections on Project MUSE., 2018)
"In Taking Baby Steps, Jody Lynee Madeira takes readers inside the infertility experience, from dealing with infertility-related emotions through forming treatment relationships with medical professionals to confronting difficult medical decisions. Based on hundreds of interviews, this book investigates how women, men, and medical professionals negotiate infertility's rocky terrain to create life and build families--a journey across personal, medical, legal, and ethical minefields that can test mental and physical health, friendships and marriages, spirituality, and financial security."--Provided by publisher.